Black Sea Observing System - Palazov, Atanas; Ciliberti, Stefania; Peneva, Elisaveta; Gregoire, Marilaure; Staneva, Joanna; Lemieux-Dudon, Benedicte; Masina, Simona; Pinardi, Nadia; Vandenbulcke, Luc; Behrens, Arno; Lima, Leonardo; Coppini, Giovanni; et al. (Frontiers in Marine Science, 2019)
The ultimate goal of modern operational oceanography are end user oriented products with high scientific quality. Beneficiaries are the governmental services, coast and offshore based enterprises and research institutions that make use of the products generated by operational oceanography. Direct users are coastal managers, shipping, search and rescue, oil spill combat, offshore industry, ports, fishing, tourism and recreation industry. Indirect beneficiaries, through climate forecasting based on ocean observations, are food, energy, water and medical suppliers. Availability of updated information on the actual state as well as forecast of marine environment is essential for the success and safety of maritime operations in the offshore industry. Various systems for the collection and presentation of marine data for the needs of different users have been developed and put in operation in the Black Sea. The systems are located both along the coast and in the open sea and the information they provide is used by both the maritime industry and the widest range of users. The Black Sea Monitoring and Forecasting Centre in the frame of the Copernicus Marine Service is providing regular and systematic information about the physical state of the ocean, marine ecosystem and wave conditions in the Black Sea area, assimilating observations, keeping efficient operations, advanced technology and high quality modeling products. Combining and optimizing in-situ, remote sensing, modeling and forecasting into a Black Sea observing system is a task that has to be solved, and that will allow to get a more complete and comprehensive picture of the state of the marine environment as well as to forecast future changes of physical and biogeochemical state of the Black Sea and the Black Sea ecosystem.